Assortative matching, interbank markets, and monetary policy - Christian Bittner; Rustam Jamilov; Farzad Saidi (University of Bonn and University of Cologne, Reinhard Selten Institute (RSI), 2025)
We develop a quantitative macroeconomic framework with heterogeneous financial intermediaries and active liquidity management. In the model, banks manage uninsured, idiosyncratic deposit withdrawal risk through an iterative over-the-counter interbank market with endogenous intensive and extensive margins and equilibrium assortative matching based on balance sheet size. We validate our framework using administrative data from Germany encompassing the universe of bank-to-bank exposures. Our findings strongly support the presence of assortative matching in the data, thereby confirming the model's key mechanism. We show that assortative matching can inefficiently lead to reduced trading volumes and a broader region of inaction in the interbank market, a smaller and riskier banking sector, and a macroeconomy characterized by lower aggregate output. Using our empirically validated framework, we explore secular trends in interbank trading, the roles of liquidity and interest rate corridor policies, and the impact of deposit market power.
Keywords: E44; E52; G20; G21; 330; heterogeneous banks; interbank markets; monetary policy; liquidity policy